(untitled) (Research, Society and Development, 2022)
The Jamari National Forest (Flona) has been showing frequent fires with an occupation component, mainly in its buffer zone, in the context of the ecological corridor of protected areas in Rondônia, which is being affected by human activity related to the expansion of the agricultural frontier of the “Arc of Deforestation” of the Amazon, associated with the permission of the continuity of the cassiterite mining activity inside the Flona, started in the 1960s. In this context, this work aims to analyze the distribution of hotspots in the Jamari Flona do and its buffer zone. To achieve the proposed objective, the analysis of the spatial and temporal distribution of heat values was used the INPE fire database, showing a high number of hotspots, mainly in the buffer zone in Flona, due to the indiscriminate use of fires in the 18 years of analysis (2000 to 2017). Decrease in the annual variations of these foci occurred with the publication of environmental legislation, with 143 incidences (95.3%) in Jamari Flona, in the first 8 years of analysis (2000 to 2007), and 7 (4.6%) in the 10 years subsequent analysis (2008 to 2017). In the buffer zone, there were 2324 incidences (52.5%) in the first 6 years of analysis (2000 to 2005), and 2104 incidences (47.5%) in the following 12 years (2006 to 2017). The results show that the occurrences of fires as a component of occupation are related to the intense regional human pressure in the ecological corridor of protected areas in Rondônia that the Flona is part of, with the influence of environmental legislation and interference from cassiterite mining activities.